Prioritizing isolation precautions: a patient-centered approach to infection prevention and control - Emine Alp Meşe; Elena Carrara; Ermira Tartari; Nico T. Mutters; Constantinos Tsioutis; Gabriel Birgand; Evelina Tacconelli (Antimicrobial Stewardship & Healthcare Epidemiology)
Healthcare-associated infections (HAIs) and multidrug-resistant (MDR) pathogens present significant challenges to global health, exacerbated by emerging threats such as SARS-CoV-2 and the growing immunocompromised population. While isolation precautions are critical for infection prevention and control (IPC), their indiscriminate application can strain resources and impact patient well-being. This review proposes a patient-centered framework for optimizing isolation strategies by integrating pathogen-related factors, individual patient risks, and healthcare facility resources to optimize isolation precautions. By incorporating targeted risk assessments, advanced analytics (e.g., omics and machine learning), and infection preventionist leadership, this approach aligns isolation measures with clinical and operational realities. It aims to enhance IPC efficacy while balancing patient needs and resource efficiency. We highlight strategies to ensure isolation precautions remain evidence-based, adaptable, and sustainable within healthcare settings. A patient-focused approach to isolation improves both infection prevention and overall quality of patient care.